Silica hollow core microstructured fibers for beam delivery in industrial and medical applications - Shephard, Jonathan D.; Urich, Artur; Carter, Richard M.; Jaworski, Piotr; Maier, Robert R. J.; Belardi, Walter; Yu, Fei; Wadsworth, William J.; Knight, Jonathan C.; Hand, Duncan P. (Frontiers in Physics, 2015)
The focus of this review is our recent work to develop microstructured hollow core fibers for two applications where the flexible delivery of a single mode beam is desired. Also, a review of other fiber based solutions is included. High power, short-pulsed lasers are widely used for micro-machining, providing high precision and high quality. However, the lack of truly flexible beam delivery systems limits their application to the processing of relatively small planar components. To address this, we developed hollow-core optical fibers for the 1 μm and green wavelength ranges. The hollow core overcomes the power delivery limitations of conventional silica fibers arising from nonlinear effects and material damage in the solid core. We have characterized such fibers in terms of power handling capability, damage threshold, bend loss and dispersion, and practically demonstrated delivery of high peak power pulses from the nanosecond to the femtosecond regime. Such fibers are ideal candidates for industrial laser machining applications. In laser surgical applications, meanwhile, an Er:YAG laser (2.94 μm) is frequently the laser of choice because the water contained in tissue strongly absorbs this wavelength. If this laser beam is precisely delivered damage to surrounding tissue can be minimized. A common delivery method of surgical lasers, for use in the operating theatre, is articulated arms that are bulky, cumbersome and unsuitable for endoscopic procedures. To address this need for flexible mid-IR delivery we developed silica based hollow core fibers. By minimizing the overlap of the light with glass it is possible to overcome the material absorption limits of silica and achieve low attenuation. Additionally, it is possible to deliver pulse energies suitable for the ablation of both hard and soft tissue even with very small bend radii. The flexibility and small physical size of systems based on these fibers will enable new minimally invasive surgical procedures.